2017
DOI: 10.5455/medarh.2017.71.316-319
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Incidence of Stroke, Myocardial infarction, Heart Failure and Sudden Cardiac Death in Patients with Atrial Fibrillation

Abstract: Introduction:Atrial fibrillation represents the most common cardiac arrhythmia in clinical practice. By year 2030, 14–17 million AF patients are anticipated in the European Union. Atrial fibrillation remains one of the major causes of stroke, heart failure, sudden death all over the world.Research Objectives:The objective of our study is to determine the cardiac and cerebrovascular events (myocardial infarction, heart failure, stroke, sudden cardiac death) and their cumulative incidence during 11 years follow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 26 publications
(15 reference statements)
1
12
0
Order By: Relevance
“…The Jordan AF study represents the first contemporary study that addresses management practices and major cardiovascular events after one-year of follow-up in a relatively large Middle Eastern cohort of patients enrolled in the era of an increasing utilization of the newer OACs to prevent stroke and SE. The principal findings of the study are as follows: (i) the majority of AF patients (9 of 10) had NVAF; (ii) the majority of patients with NVAF had high-risk CHA2DS2-VASc score (∼80%); and (iii) rates of incidence of major cardiovascular events at one-year of follow-up were comparable to those reported by studies from other regions in the world [ 22 24 ].…”
Section: Resultssupporting
confidence: 61%
“…The Jordan AF study represents the first contemporary study that addresses management practices and major cardiovascular events after one-year of follow-up in a relatively large Middle Eastern cohort of patients enrolled in the era of an increasing utilization of the newer OACs to prevent stroke and SE. The principal findings of the study are as follows: (i) the majority of AF patients (9 of 10) had NVAF; (ii) the majority of patients with NVAF had high-risk CHA2DS2-VASc score (∼80%); and (iii) rates of incidence of major cardiovascular events at one-year of follow-up were comparable to those reported by studies from other regions in the world [ 22 24 ].…”
Section: Resultssupporting
confidence: 61%
“…Presence of persistent AF was associated with progressive heart failure (LVEF <35%). Large-scaled population-based studies demonstrated a higher incidence of SCD at long-term follow-up in AF patients 28,29 . Furthermore, virtually all risk prediction scores for primary preventive ICD therapy found AF to be a strong risk factor in patients with LVEF <35% 30,31 .…”
Section: Discussionmentioning
confidence: 96%
“…The two entities have a bidirectional relationship, and they share similar predisposing factors. The main pathophysiological mechanisms of hypertension-related AF include hypertension-induced LVH and subsequent LA enlargement and remodeling, while activation of the sympathetic nervous system and the renin-angiotensin-aldosterone system (RAAS) also contribute to the development of AF (13) . AF during hypertension increases the risk of thromboembolic complications and heart failure.…”
Section: Discussionmentioning
confidence: 99%